Individual variation in winter supplementary food consumption and its consequences for reproduction in wild birds. (4th April 2016) - Crates, Ross A.; Firth, Josh A.; Farine, Damien R.; Garroway, Colin J.; Kidd, Lindall R.; Aplin, Lucy M.; Radersma, Reinder; Milligan, Nicole D.; Voelkl, Bernhard; Culina, Antica; Verhelst, Brecht L.; Hinde, Camilla A.; et al.
Abstract : The provision of wild birds with supplementary food has increased substantially over recent decades. While it is assumed that provisioning birds is beneficial, supplementary feeding can have detrimental 'carry‐over' effects on reproductive traits. Due to difficulties in monitoring individual feeding behaviour, assessing how individuals within a population vary in their exploitation of supplementary food resources has been limited. Quantifying individual consumption of supplementary food is necessary to understand the operation of carry‐over effects at the individual level. We used Radio Frequency Identification (RFID) technology and automated feeders to estimate individual consumption of supplementary winter food in a large wild population of great tits Parus major and blue tits Cyanistes caeruleus . Using these data, we identified demographic factors that explained individual variation in levels of supplementary food consumption. We also tested for carry‐over effects of supplementary food consumption on recruitment, reproductive success and a measure of survival. Individual variation in consumption of supplementary food was explained by differences between species, ages, sexes and years. Individuals were consistent across time in their usage of supplementary resources. We found no strong evidence that the extent of supplementary food consumption directly influenced subsequent fitness parameters. Such effects may instead result from supplementary food influencing population demographics by enhancing the survival and subsequent breeding of less competitive individuals, which reduce average breeding parameters and increase density‐dependent competition. Carry‐over effects of supplementary feeding are not universal and may depend upon the temporal availability of the food provided. Our study demonstrates how RFID systems can be used to examine individual‐level behaviour with minimal effects on fitness.